2011
DOI: 10.1007/s10103-011-0896-z
|View full text |Cite
|
Sign up to set email alerts
|

Light-curing of dental resins with GaN violet laser diode: The effect of photoinitiator on mechanical strength

Abstract: The purpose of this study was to evaluate whether a Gallium Nitride (GaN) -based violet laser diode (VLM500) could be used as a light source for light-cured dental resins. Three experimental unfilled resins containing different photoinitiators (camphorquinone, CQ; phenyl propanedione, PPD; or mono acylphosphineoxide, MAPO) were evaluated. These resins were lightcured with a VLM500 laser diode, and their ultimate micro-tensile strengths (μTS) were compared to those cured with three different LED light sources (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Signaling pathways that include both portal fibroblasts and cholangiocytes as participants may include polarity, TGFβ, Hedgehog, and Notch signaling pathways; these may involve mature cells or peribiliary stem cells. [48][49][50][51][52] Jhandier et al have shown that portal fibroblasts and myofibroblasts, acting via extracellular nucleotides, regulate cholangiocyte proliferation. 53 This function may be particularly important in intrahepatic cholangiocarcinoma, a highly desmoplastic tumor with accumulation of myofibroblasts.…”
Section: Portal Fibroblastsmentioning
confidence: 99%
“…Signaling pathways that include both portal fibroblasts and cholangiocytes as participants may include polarity, TGFβ, Hedgehog, and Notch signaling pathways; these may involve mature cells or peribiliary stem cells. [48][49][50][51][52] Jhandier et al have shown that portal fibroblasts and myofibroblasts, acting via extracellular nucleotides, regulate cholangiocyte proliferation. 53 This function may be particularly important in intrahepatic cholangiocarcinoma, a highly desmoplastic tumor with accumulation of myofibroblasts.…”
Section: Portal Fibroblastsmentioning
confidence: 99%
“…Regardless of the difference in absorption, the µTS of both FL-Bond II and Tokuso Mac Bond II when cured using the VLM 500 unit was almost similar as when the adhesives were cured with the LED Curenos and G-light Prima light-curing units. In our previous study, the µTS of a 1% CQ-containing unfilled resin that was cured with the LED G-Light Prima unit used in 'PL mode' (only emission by the violet LED with an output of 52 mW/cm 2 ), was significantly lower than when the resin was cured with the LED Curenos unit and the LED G-Light Prima unit used in 'Normal mode' [42]. However, the µTS did not differ when the resin was cured either using the VLM 500 unit, the LED Curenos unit or the LED G-Light Prima unit used in 'Normal mode' [42].…”
Section: Discussionmentioning
confidence: 90%
“…In our previous study, the µTS of a 1% CQ-containing unfilled resin that was cured with the LED G-Light Prima unit used in 'PL mode' (only emission by the violet LED with an output of 52 mW/cm 2 ), was significantly lower than when the resin was cured with the LED Curenos unit and the LED G-Light Prima unit used in 'Normal mode' [42]. However, the µTS did not differ when the resin was cured either using the VLM 500 unit, the LED Curenos unit or the LED G-Light Prima unit used in 'Normal mode' [42]. These data therefore suggested that the lower absorption coefficient of CQ for violet light can be compensated by increasing the power density.…”
Section: Discussionmentioning
confidence: 90%
“…Their emission range is from 390 to 500 nm, with a peak wavelength of 470–480 nm. Because the absorbance wavelength of camphorquinone (CQ), which is added to most light-cured restorative materials, has been reported as 430–490 nm with a peak at 468 nm, the emission ranges of these LCUs are likely to be optimal for CQ [25, 26]. D-Lux 2000 can be selected with either a turbo light guide or a conventional straight guide.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the G-Light Prima and the Bluephase G2 are “dual-wave” LCUs that contain not only blue LEDs but also supplementary violet LED(s) to polymerize 1-phenyl-1,2-propanedione (PPD) and 2,4,6-trimethylbenzoyl diphenyl-phosphine oxide (Lucirin TPO) effectively [25, 26]. For the Pencure and the G-Light Prima, the displayed power densities in the Bluephase Meter and the Cure Rite were approximately 30% and 25% lower, respectively, than those of the USR-45 spectroradiometer.…”
Section: Discussionmentioning
confidence: 99%